Citra Perempuan dan Ketimpangan Gender dalam Sali: Kisah Seorang Wanita Suku Dani - Siswanto Siswanto (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This paper give reflection to the reader about the image of women and injustice experienced by women in the Dani tribe without being able to defend against the injustices suffered by the female characters in the novel. For example, when a wife asks her husband's responsibility to work to meet the needs of family life, but received the invective, scolding, and even violence from her husband. In addition, women also serve as sexual objects by men without being able to provide resistance, causing a prolonged trauma. Injustices experienced by women is also still frequently occur until now, whether it is injustice in the menage, sexual or economy. This makes the speaker choose the topic of gender inequality against women in the novel Sali: Kisah Seorang Wanita Suku Dani by Dewi Linggasari. In  this paper, the speaker uses feminist literary studies, by considering the aspects of feminism.